Social Hierarchy in Kinema Citrus’s The Rising of the Shield Hero (2019) - Muhammad Rizqullah Afflah, Ricco (LITERA KULTURA : Journal of Literary and Cultural Studies, 2025)
This study examines the representation of social class in the anime The Rising of the Shield Hero within the framework of Pierre Bourdieu's theory of the reproduction of social life. The study examines comments on the Kingdom of Melromarc's hierarchical structure that influences the protagonists and what can be maintained in the ruling class, especially in the Church of Nobility and the Three Heroes. The study uses a qualitative content analysis method and focuses on the narrative elements in the anime, the interaction between characters, and the relationship between heroes. The result is the rigid hierarchical structure of Melromarc, which strengthens economic, cultural, and social capital, limits social mobility, and maintains the dominance of the elite. These studies are consistent with the concept of life and Bourdieu's square, illustrating the street power commentary on visible and invisible social mechanisms.